Impact of Technological Adoption, Innovation Management, and Market Demand on Competitive Advantage - Safitri, Camelia; Miranda, Mira (International Journal of Business, Law, and Education, 2024)
This study investigates the impact of technological adoption, innovation management, and market demand on competitive advantage among firms in Indonesia. Using a sample of 400 companies across various industry sectors, this research employs multiple regression analysis to determine the relationship between these variables. The results indicate that technological adoption, innovation management, and market demand significantly and positively influence competitive advantage. The findings suggest that firms that effectively adopt technology, manage innovation, and respond to market demands are more likely to achieve superior competitive positioning. These insights provide practical implications for managers and policymakers aiming to enhance business performance and competitive edge. Future research should further explore these dynamics in different contexts and consider additional influencing factors to enrich the understanding of competitive advantage.